Food Safety and Food Resources in the Post-COVID-19 World - Şahin, Kazım; Hayaloglu, Ali Adnan (Tuba-Turkish Acad Sciences, 2020)
SARS-CoV-2, which was seen for the first time in Wuhan China in December 2019, is the cause of coronavirus disease (COVID-19). It led to pandemic and resulted in the death of important numbers of people wordwide. Despite the large scale of the pandemic, there has been no report or data of transmission of COVID-19 via consumption of food to date. But food could also lead to indirect contamination through if infected person touch it. This is why everybody should follow the recommendations of public health authorities on the washing of hands. In this study, the potential interaction of SARS-CoV-2 with food products and potential risks, the effects in food system, the practices that the food handlers can follow to prevent the contamination and the spread of the virus, what is the importance of good hygiene practices in food safety in this pandemic, the role of consumers in this process are discussed and it has underlined that the importance of safety and good hygiene practices in pandemi.
Keywords: SARS-CoV-2; COVID-19; good hygiene practices; food safety; pandemic